Cultural Harmony In Taste: Acculturation Of Chinese-Banjar Culinary Culture In Banjarmasin City - Muhammad William Syabani; Rahman Hakim, Arif (Program Studi Sosiologi, FISIP ULM, 2025)
This study examines the acculturation of Chinese and Banjar cultures in the culinary traditions of Banjarmasin. Using a qualitative ethnographic approach, data were collected through observation, interviews, literature studies, and documentation. John W. Berry's acculturation theory serves as the analytical framework to understand the blending of these cultures. The findings reveal that Chinese culinary elements such as Jao To and noodles have been adapted, resulting in unique Banjar dishes like Soto Banjar and Mie Habang. A notable fusion is Sup Mutiara, a dish that exemplifies cultural integration. Additionally, Banjar influences appear in Chinese rituals such as Cap Go Me and Ceng Beng, demonstrated by offerings like Lontong Cap Go Me and wadai banjar. The acculturation process is attributed to historical interactions and mutual acceptance between Chinese and Banjar communities, highlighting the openness of Banjar society. This research underscores the reciprocal impact of cultural exchange on Banjarmasin's culinary diversity, positioning the city as a multicultural hub. Keywords: Acculturation, Culinary, Chinese-Banjar.